2022
DOI: 10.1186/s10195-022-00636-9
|View full text |Cite
|
Sign up to set email alerts
|

Imageless navigation for primary total hip arthroplasty: a meta-analysis study

Abstract: Background There has been a growing interest in imageless navigation for primary total hip arthroplasty (THA). Its superiority over standard THA is debated. This meta-analysis compared surgical duration, implant positioning, Harris Hip Score and rate of dislocation of imageless navigation versus conventional THA. Methods The present study was conducted according to the PRISMA 2020 guidelines. All the clinical trials comparing imageless navigation v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 48 publications
1
19
1
Order By: Relevance
“…Including this mean deviation, the values were still within the safe zones [ 90 ]. Another meta-analysis published by Migliorini et al in 2022 found slightly lower leg length discrepancies for navigated THA, but similar results for cup positioning and dislocation rates when comparing conventional and navigated THA [ 85 ].…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Including this mean deviation, the values were still within the safe zones [ 90 ]. Another meta-analysis published by Migliorini et al in 2022 found slightly lower leg length discrepancies for navigated THA, but similar results for cup positioning and dislocation rates when comparing conventional and navigated THA [ 85 ].…”
Section: Discussionmentioning
confidence: 90%
“…Furthermore, increased spinopelvic mobility has been found to be a risk factor for errors in cup positioning, yet this has only been reported when operating the patient in lateral decubitus position [ 84 ]. Imageless navigation is associated with longer operation time compared to conventional THA [ 85 ]. Brown et al reported additional time demand especially during the pre-operative phases, specifically to re-drape and re-position the patient after the placement of the initial tracker and to register the landmarks [ 86 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to RA-THA platforms, imageless computer-navigation THA systems have also been developed in recent years to improve the accuracy of component placement. 27,28 These technologies are layered onto DAA THA to aid with acetabular cup positioning, and, similar to surgical robots, have been studied for learning curve during adoption. Valsamis et al found the learning curve of an imageless computer-navigated THA system was 15 cases, 29 while Thorey et al…”
Section: Phasementioning
confidence: 99%
“…An imageless navigation systems is a computer-assisted procedure, where the surgeon uses three-dimensional sensors to detect anatomical features. An important meta-analysis published later in 2022 included all the clinical trials comparing imageless navigation versus conventional primary THA [31]. The analysis consisted of 21 studies (2706 procedures) aiming to compare cup inclination and anteversion, leg length discrepancy, surgical duration, Harris Hip Score, and rate of dislocation between the two THA approaches.…”
Section: Navigation Systems In Thamentioning
confidence: 99%